(untitled) (SAARC Journal of Agriculture, 2021)
Eleven rice hybrids including two check varieties were evaluated to approximate their genetic variability, heritability and genetic advance for ten quantitative traits. The analysis of variance illustrated that all the quantitative traits differed significantly indicating that enough variation is presenting the studied materials. Among the desirable quantitative traits number of filled spikelet’s per panicle was found to have highest both phenotypic and genotypic variance followed by total number of spikelet’s per panicle. Almost all the characters showed a little variation between PCV and GCV revealing little influence of the environment on the expression of traits. High phenotypic and genotypic variance coupled with high heritability and high genetic advance was observed for number of filled spikelet’s per panicle, total number of spikelet’s per panicle, plant height and number of unfilled spikelet’s per panicle. Such findings stipulated that these traits were governed by additive gene actions which are fixable and these traits may be accounted for reliable index of selection. The genotypes G3 (IR79156A × EL108R) and G6 (IR79156A × EL253R) were selected as high response superior promising rice hybrids for achievable yield advantage 49% and 23%, respectively over best check varieties. Therefore, the G3 and G6 are proposed to be extensively evaluated for further trial of variety release. SAARC J. Agri., 18(2): 39-49 (2020)